Theoretical Aspects of Financial Security of Join-stock Companies (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The author made a critical review of approaches of the scientists for understanding the concepts of «financial security of join-stock companies». Based on the results of the study author made own proposals for understanding the concept of join-stock enterprises’ financial security. Also in the article defined main characteristics of financial security of join-stock enterprises. In the article are rased the problems of necesserity of researching of the financial security of join-stock companies and its functions.
Keywords: join-stock companies, financial security, indicators of financial security, functions of financial security